Manajemen Pendidikan Lembaga Non-Formal Berbasis Nilai Al Quran dan Hadist - Ndanda Ambarawadi; Kojin Kojin; Nur Efendi (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to analyze the implementation of educational management of non-formal institutions based on the values of the Qur'an and Hadith and identify relevant management models to improve the effectiveness of institutional management. The background of the research shows that non-formal education has a strategic role, but its management practices still face various obstacles, such as limited human resources, weak planning, and a lack of innovation. This research uses a literature study method by examining accredited journals, research reports, and scientific papers related to non-formal education management and Islamic management perspectives. The analysis was carried out through a content approach to find the main themes that formed the pattern of implementation of Qur'an and Hadith values in the management function. The results of the study show that the values of trust, deliberation, ihsan, and hisbah play an important role in strengthening the functions of planning, organizing, implementing, and supervising in non-formal institutions. The discussion emphasized that the integration of these values is able to answer managerial weaknesses empirically and produce a more effective, participatory, and Islamic management model. This research makes a conceptual contribution to the development of the management of non-formal institutions in Indonesia. In conclusion, management based on the values of the Qur'an and Hadith not only improves the quality of governance of non-formal institutions but also strengthens the character and spirituality of education as a whole.